2009
DOI: 10.1038/nature07765
|View full text |Cite
|
Sign up to set email alerts
|

A mechanosensitive transcriptional mechanism that controls angiogenesis

Abstract: Angiogenesis is controlled by physical interactions between cells and extracellular matrix as well as soluble angiogenic factors, such as VEGF. However, the mechanism by which mechanical signals integrate with other microenvironmental cues to regulate neovascularization remains unknown. Here we show that the Rho inhibitor, p190RhoGAP, controls capillary network formation in vitro and retinal angiogenesis in vivo by modulating the balance of activities between two antagonistic transcription factors – TFII-I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
520
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 484 publications
(545 citation statements)
references
References 48 publications
20
520
4
1
Order By: Relevance
“…Importantly, this novel angiogenesis signalling pathway is sensitive to ECM elasticity as well as VEGF (Figure 7c). [138] This work suggested that an appropriate level of ECM stiffness might be required for optimal VEGFR2 expression and vascular development in vitro and in vivo. More recently, Picart and colleagues investigated mechanisms by which BMP-2 presented from surfaces is internalized by cells, and found this process to be also dependent on the stiffness of the substrate from which the GF was presented, with higher internalisation rates on soft substrates.…”
Section: The Interplay Between Growth Factor Signalling and Mechanotrmentioning
confidence: 95%
“…Importantly, this novel angiogenesis signalling pathway is sensitive to ECM elasticity as well as VEGF (Figure 7c). [138] This work suggested that an appropriate level of ECM stiffness might be required for optimal VEGFR2 expression and vascular development in vitro and in vivo. More recently, Picart and colleagues investigated mechanisms by which BMP-2 presented from surfaces is internalized by cells, and found this process to be also dependent on the stiffness of the substrate from which the GF was presented, with higher internalisation rates on soft substrates.…”
Section: The Interplay Between Growth Factor Signalling and Mechanotrmentioning
confidence: 95%
“…Previous studies have implicated a small GTPase, RhoA, as an important molecular player in regulation of cell responses to mechanical cues, as well as in controlling cell morphology, and interaction with other cells [6,32]. Cardiac tissue generation and morphogenesis involve all the above processes.…”
Section: The Critical Role Of P190rhogap In Cardiac Endothelial Cellmentioning
confidence: 99%
“…In other words, the mechanical properties of the surrounding environment, such as matrix elasticity, can not only permit or enhance certain predefined differentiation outcomes but also determine which lineage is adopted by multipotent stem or precursor cells [8]. In addition, mechanical cues have long been known to play a role in tissue morphogenesis in various settings, including luminal morphogenesis of differentiated endothelial cells [6], striated morphogenesis of muscle cells [9], and polarized separation of basal lamina and apical membrane in epithelial cells [12]. Therefore, it is instructive to explore whether the seemingly independent phenomena involved in tissue repair: proliferation of stem cells, differentiation into somatic cells, and tissue morphogenesis might be regulated directly by the extracellular mechanical cues.…”
Section: Integrative Control Of Tissue Development and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations